Pivotal Role of Carbohydrate Sulfotransferase 15 in Fibrosis and Mucosal Healing in Mouse Colitis - Suzuki, Kenji; Arumugam, Somasundaram; Yokoyama, Junji; Kawauchi, Yusuke; Honda, Yutaka; Sato, Hiroki; Aoyagi, Yutaka; Terai, Shuji; Okazaki, Kazuichi; Suzuki, Yasuo; Mizumoto, Shuji; Sugahara, Kazuyuki; et al. (PLoS ONE, 2016)
Induction of mucosal healing (MH) is an important treatment goal in inflammatory bowel disease (IBD). Although the molecular mechanisms underlying MH in IBD is not fully explored, local fibrosis would contribute to interfere mucosal repair. Carbohydrate sulfotransferase 15 (CHST15), which catalyzes sulfation of chondroitin sulfate to produce rare E-disaccharide units, is a novel mediator to create local fibrosis. Here we have used siRNA-based approach of silencing CHST15 in dextran sulfate sodium (DSS) induced colitis in mice, human colon fibroblasts and cancer cell lines. In a DSS-induced acute colitis model, CHST15 siRNA reduced CHST15 mRNA in the colon, serum IL-6, disease activity index (DAI) and accumulation of F4/80+ macrophages and ER-TR7+ fibroblasts, while increased Ki-67+ epithelial cells. In DSS-induced chronic colitis models, CHST15 siRNA reduced CHST15 mRNA in the colon, DAI, alpha-smooth muscle actin+ fibroblasts and collagen deposition, while enhanced MH as evidenced by reduced histological and endoscopic scores. We also found that endoscopic submucosal injection achieved effective pancolonic delivery of CHST15 siRNA in mice. In human CCD-18 Co cells, CHST15 siRNA inhibited the expression of CHST15 mRNA and selectively reduced E-units, a specific product biosynthesized by CHST15, in the culture supernatant. CHST15 siRNA significantly suppressed vimentin in both TGF-ß-stimulated CCD18-Co cells and HCT116 cells while up-regulated BMP7 and E-cadherin in HCT116 cells. The present study demonstrated that blockade CHST15 represses colonic fibrosis and enhances MH partly though reversing EMT pathway, illustrating a novel therapeutic opportunity to refractory and fibrotic lesions in IBD.
EVALuna2:2164